2014
DOI: 10.1111/add.12501
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tobacco control television advertising in changing tobacco use in England: a population-based cross-sectional study

Abstract: AimTo examine whether government‐funded tobacco control television advertising shown in England between 2002 and 2010 reduced adult smoking prevalence and cigarette consumption.DesignAnalysis of monthly cross‐sectional surveys using generalised additive models.SettingEngland.ParticipantsMore than 80 000 adults aged 18 years or over living in England and interviewed in the Opinions and Lifestyle Survey.MeasurementsCurrent smoking status, smokers' daily cigarette consumption, tobacco control gross rating points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Considering the influence of these critical factors in the success of tobacco control campaigns aired in the United Kingdom over the past 10 years, the recent papers by Sims et al [4] and Langley et al [5] are a welcome addition to the literature. Sims and colleagues' study [4] indicates that each person in the population needs to be exposed to approximately four anti-smoking advertisements per month to result in a detectable impact on smoking prevalence. These findings have a remarkably high degree of consistency with previous studies from Australia [6,7] and the United States [8,9], which indicate that moderate to high levels of intensity (i.e.…”
Section: Commentary On Sims Et Al (2014) and Langley Et Al (2014): mentioning
confidence: 99%
“…Considering the influence of these critical factors in the success of tobacco control campaigns aired in the United Kingdom over the past 10 years, the recent papers by Sims et al [4] and Langley et al [5] are a welcome addition to the literature. Sims and colleagues' study [4] indicates that each person in the population needs to be exposed to approximately four anti-smoking advertisements per month to result in a detectable impact on smoking prevalence. These findings have a remarkably high degree of consistency with previous studies from Australia [6,7] and the United States [8,9], which indicate that moderate to high levels of intensity (i.e.…”
Section: Commentary On Sims Et Al (2014) and Langley Et Al (2014): mentioning
confidence: 99%
“…This (prospective scenario 1) was therefore planned to be designed on the basis of these social marketing campaigns. The relative increase in quit attempts is the measure of effectiveness of interventions included in the EQUIPT model, and we used the value for this model input from an English population‐based cross‐sectional study 18.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing body of international evidence that MMCs can prevent both the uptake of smoking in young people and promote smoking cessation in adults 2, 3, 4, 5, 6. Most recently, evidence from England has shown that TV MMCs are effective in triggering quitting behaviour in adults and were responsible for an 11.2% decline in cigarette consumption and 13.5% of the decline in prevalence between 2002 and 2009 7. However, English studies also found that while the broadcast of TV MMCs was associated with an increase in calls to the national Quitline, there was no significant impact on either prescribed or over‐the‐counter (OTC) nicotine replacement therapy (NRT) 8.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, both types of campaign had an effect upon important measures of quitting behaviour—quitline calls, quit attempts and prevalence. However, consumption among smokers was affected only by campaigns evoking negative emotions 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation